2010
DOI: 10.12660/joscmv3n1p34-54
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the relationship between logistics complexity and supply chain objectives and decision areas in large companies operating in Brazil

Abstract: This paper reports an attempt to explore the relationships between logistics complexity and supply chain management (SCM) objectives and decision areas in large manufacturing companies operating in Brazil. Literature review is conducted, followed by survey research data (using a sample of 108 large companies operating in Brazil) analysis using cluster analysis, factor analysis and binary logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Hypothesis 7: Forecasting in uences LMIS effectiveness Forecasting involves planning of SCM activities to improve SCM practices. According to this study that compared the relationship between Logistics and supply chain objectives [22], it was con rmed that forecasting was signi cantly related to supply chain performance.…”
Section: Hypothesis 5: Service Quality In Uence Lmis Effectivenessmentioning
confidence: 88%
“…Hypothesis 7: Forecasting in uences LMIS effectiveness Forecasting involves planning of SCM activities to improve SCM practices. According to this study that compared the relationship between Logistics and supply chain objectives [22], it was con rmed that forecasting was signi cantly related to supply chain performance.…”
Section: Hypothesis 5: Service Quality In Uence Lmis Effectivenessmentioning
confidence: 88%
“…Hypothesis11: Production in uences LMIS effectiveness Good products aid to increase customers' demand. A study [22] observed that production leads to the receptiveness of fast delivery of nal product to the customer.…”
Section: Hypothesis 5: Service Quality In Uence Lmis Effectivenessmentioning
confidence: 99%
“…In the categorization of the decisions that VA systems are intended to support, we have also used the SC decision area categorization provided by Wanke et al [40]. These authors provided the most relevant decision areas of the SC management based on the literature.…”
Section: A Va Application Areas Decisions and Required Datamentioning
confidence: 99%
“…On the other hand, the SCOR model activities are encompassing the SC processes' decisions and the presentation of our results based on this model provides a supplementary categorization for the decision areas. Therefore, the categorization of the decisions can be observed from two dimensions, first, the SCOR model activities, and second, the decision area categorization provided by Wanke et al [40]. Figure 2 shows the categorization of the studies into different decision areas provided by Wanke et al…”
Section: A Va Application Areas Decisions and Required Datamentioning
confidence: 99%